Assessment of the endoscopic retrograde cholangiopancreatography grading system: A prospective study from a tertiary care center - Torun, Serkan; Parlak, Erkan; Yıldız, Hakan; Dişibeyaz, Selçuk; Ödemiş, Bülent; Beyazıt, Yavuz; Şaşmaz, Nurgül; Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The American Society for Gastrointestinal Endoscopy (ASGE) endoscopic retrograde cholangiopancreatography (ERCP) grading system was proposed but has not been fully evaluated with prospective clinical studies. In this study, we aimed to evaluate the effectiveness of the ERCP difficulty grading system for predicting success and adverse event rates related to the procedure. Materials and Methods: A total of 1057 ERCP procedures performed on 752 patients were included in the present study. The complexity grades of the procedures were recorded according to the ASGE grading system. Specific complications of ERCP (pancreatitis, cholangitis, bleeding, and perforation) were also defined and graded. Results: The procedure difficulty was determined as 1st degree in 153 patients (14.4%), 2nd degree in 498 patients (47.1%), 3rd degree in 271 (25.6%), and 4th degree in 135 patients (12.7%). The success rate for the entire procedures was 88.4%. The success rate for 1st degree procedures was 99.3%, 97.2% for 2nd degree procedures, 86.7% for 3rd degree procedures, and 46.7% for 4th degree procedures (p<0.005). When the difficulty of the procedures increased from 1 to 4, the adverse event rates increased from 1.3% to 10.4%. Conclusion: The findings support the evidence that the difficulty degrees of ERCP procedures can help predict the success and complication rates of the procedure. Because of the increased rates of failure and complications in more difficult cases, the procedures should be performed by experienced endoscopists in advanced centers.